Effect of Particle Size Distribution on Ammonium Sulphate Dried in a Rotary Dryer - Susianto, Susianto; Altway, Ali; Kuswandi, Kuswandi; Margono, Margono (IPTEK The Journal for Technology and Science, 2010)
The aim of this work is to study theoretically, by mathematical model development, the effect of particle size distribution on the performance of rotary dryer to dry ammonium sulphate fertilizer assuming plug flow with axial dispersion pattern (PFDA model) for solid particle flow. The mathematical model development was carried out by combining the drying processes model with particle size distribution model. Particle size distribution models used are Rosin-Rommler model and Gamma distribution model. For simplicity, the model of drying processes of solid particles in the rotary dryer was developed by assuming of uniform air conditions (temperature and humidity) along the rotary dryer as in the entry conditions. The resulting differential equations were solved analytically under Matlab 6.1 facility.Since this model, solid hold up, and axial dispersion number were obtained from empirical correlations in the literatures. The drying rate of ammonium sulphate fertilizer in rotary dryer was estimated using isothermal diffusion model with effective diffusivity of moisture in the particle obtained from previous study [2]. Using Gamma function distribution, this research showed that for the value of the coefficient of variance (CV) less than 0.5, particle size distribution does not have significant effect on dryer performance. For the value of CV greater than 0.5, the dryer performance increase (or outlet solid moisture content decrease) with increasing the value of CV. The application of Rosin-Rammler model gives lower prediction of outlet solid moisture content compared to the application of Gamma function model.